2004
DOI: 10.2193/0091-7648(2004)32[554:comdda]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of mule deer day-bed and forage sites in current-condition and restoration-treated ponderosa pine forest

Abstract: We characterized microhabitat (structure and microclimate) at 236 mule deer (Odocoileus hemionus) day‐beds, 152 diurnal forage sites, and 439 random locations during summers of 1998–2000. Our objectives were to 1) identify important microhabitat characteristics of day‐beds and forage sites in untreated forest, 2) compare relative availability of bed and forage sites having these characteristics between forest types, 3) determine whether mule deer selected either forest type disproportionately for these activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 24 publications
2
21
1
Order By: Relevance
“…Canopy cover was a strong predictor of mule deer habitat use during summer with the highest probability of use predicted at intermediate (~40%) amounts of cover. This finding is consistent with previous studies of mule deer (Kufeld et al , Ager et al , Germaine et al ). Higher values of canopy cover provide a buffer against climatic extremes (i.e., temperature, solar radiation, and wind speed) and protection from predation, whereas lower values are often correlated with higher quantities of forage (Mysterud and Østbye ).…”
Section: Discussionsupporting
confidence: 94%
“…Canopy cover was a strong predictor of mule deer habitat use during summer with the highest probability of use predicted at intermediate (~40%) amounts of cover. This finding is consistent with previous studies of mule deer (Kufeld et al , Ager et al , Germaine et al ). Higher values of canopy cover provide a buffer against climatic extremes (i.e., temperature, solar radiation, and wind speed) and protection from predation, whereas lower values are often correlated with higher quantities of forage (Mysterud and Østbye ).…”
Section: Discussionsupporting
confidence: 94%
“…Protection from predators is especially important for females trying to ensure the successful development of their offspring (Bowyer et al, 1998;Fox and Krausman, 1994;Gerlach and Vaughan, 1991;Germaine et al, 2004;Huegel et al, 1986;Kroll, 1992;). They search for bedsites with dense cover that is mostly located between the soil and one meter above the ground (Fox and Krausman, 1994;Germaine et al, 2004). Dams are very important sites for the deer given that, in addition to providing water, the riparian vegetation offers dense cover (thermal and concealment), and these are the only places where tree species such as A. farnesiana are found (Bello et al, 2001a).…”
Section: Discussionmentioning
confidence: 99%
“…Dense bedsite cover was found to be critical to fawn survival in Montana (Riley and Dood, 1984), Arizona (Smith and LeCount, 1979) and Iowa (Huegel et al, 1986). Germaine et al (2004) found that site temperature and canopy closure were the most influential attributes in bedsite selection by deer.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Effects of temperature, particularly cold temperatures, on whitetailed deer Odocoileus virginianus have been documented in temperate environments (Beier and McCullough 1990), but the effects of heat on habitat selection in subtropical environments are unclear. To reduce heat stress, cervids commonly become inactive and bed in areas with dense vegetation canopy cover (Sargeant et al 1994, Mysterud and Østbye 1999, Germaine et al 2004, Bowyer and Kie 2009). In southern Texas where maximum daily temperatures during summer may exceed 38 C, the need for thermal cover to reduce heat stress should be a major factor influencing selection of plant communities by white-tailed deer during midday.…”
mentioning
confidence: 99%